LIPA gene mutations affect the composition of lipoproteins: Enrichment in ACAT-derived cholesteryl esters. (March 2020) - Arnaboldi, Lorenzo; Ossoli, Alice; Giorgio, Eleonora; Pisciotta, Livia; Lucchi, Tiziano; Grigore, Liliana; Pavanello, Chiara; Granata, Agnese; Pasta, Andrea; Arosio, Beatrice; Azzolino, Domenico; Baragetti, Andrea; et al.
Abstract: Background and aims: Cholesteryl ester storage disease (CESD) due to LIPA gene mutations is characterized by hepatic steatosis, hypercholesterolemia and hypoalphalipoproteinemia, exposing affected patients to an increased cardiovascular risk. Further insights into the impact of LIPA gene mutations on lipid/lipoprotein metabolism are limited. Aim of the study was to investigate the effect of carrying one or two mutant LIPA alleles on lipoprotein composition and function. Methods: Lipoproteins were isolated from 6 adult CESD patients, 5 relatives carrying one mutant LIPA allele (carriers) and 12 sex/age matched controls. Lipid profile, lipoprotein mass composition and the fatty acid distribution of cholesteryl esters (CEs) were assessed. HDL function was evaluated as the ability to promote nitric oxide release by endothelial cells. Results: Despite the lipid-lowering therapy, total cholesterol, LDL-cholesterol and triglycerides were increased in CESD patients compared to controls, while HDL-cholesterol was reduced. Carriers also displayed elevated total and LDL-cholesterol. Very low and intermediate density lipoproteins from CESD patients and carriers were enriched in CEs compared to the control ones, with a concomitant reduction of triglycerides. Fatty acid composition of CEs in serum and lipoproteins showed a depletion of linoleate content in CESD patients, due to the reduced LCAT activity. In CESD HDL, fatty acid distribution of CEs was shifted towards saturated ones, if compared to control HDL. The changes in HDL composition did not affect HDL ability to promote nitric oxide release by endothelial cells. Conclusions: LIPA gene mutations significantly affected plasma levels and lipid composition of lipoproteins, likely contributing to the increased cardiovascular risk of affected patients. Graphical abstract: Image 1 Highlights: CESD is associated with increased levels of apoB-containing lipoproteins and reduced HDL. VLDL and IDL from CESD patients and carriers of one mutant LIPA allele are enriched in CEs and depleted in TGs. The linoleate content of cholesteryl esters is reduced in the lipoproteins from CESD patients. HDL ability to promote nitric oxide release by endothelial cells is preserved in CESD.